Strengthening agricultural extension training in Nigeria, Malawi, South Africa, Uganda, and Kenya - Suvedi, Murari; Sasidhar, P. V. K.; Agwu, Ekwe Agwu; Chanza, Charity; Ukamaka, Mabel Dimelu; Liverpool-Tasie, Saweda Lenis Onipede; Anugwa, Ifeoma Quinette; Tchuwa, Frank; Davis, Kristin E.; Mangheni, Margaret Najjingo; Oywaya-Nkurumwa, Anges; von Maltitz, Lindie; et al. (Alliance for African Partnership, 2023)
To strengthen the agricultural extension curriculum, the present study was undertaken in sub-Saharan Africa covering Nigeria, Malawi, South Africa, Uganda, and Kenya during 2021-2023. The population for the study was agricultural extension professionals within these five countries drawn from universities, public- sector organizations, private- sector organizations, and NGOs. Mixed- method research design, comprising quantitative and qualitative approaches, was employed to assess the process skills and competency gaps in undergraduate (UG) agricultural extension curricula with the following research questions and objectives: